Biliary Tract Disease in Pediatric Surgery Department: 10 Years Experience in Khouzestan-IRAN - Shahnam Askarpour; Hazhir Javaherizadeh; Fahime Abaforoush (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2018)
Introduction: Our aim was to evaluate clinical manifestation, and outcome of biliary tract disease in patients referred for treatment to two referral centers of pediatric surgery of Ahvaz. Materials and Methods: In this retrospective study, patients with biliary tract disease admitted in Imam Khomeini and Abuzar hospitals (two referral centers for pediatric surgery in Ahvaz) during a 10-year period starting from March 2000 were evaluated. Age, sex, clinical manifestation, type of surgery, imaging finding, laboratory finding, duration of hospital stay, blood product infusion, and mortality rates were recorded. Data was analyzed with SPSS Ver 13.0(Chicago, IL, USA). We used Chi-square and t-test for comparison. Results: Twenty cases (m=13, f=7) of biliary atresia were included in this study. Mean age at the time of diagnosis and operation was 82.11 days (30 days- 6.5 months). Jaundice (100%), acholic stool (55%), and dark brown urine (55%) were the most frequent clinical manifestation in patients with biliary atresia. Of all cases, 17 patients underwent surgery. Eighteen cases (m=11, f=7) of cholecystitis were included in this study. Abdominal pain (72%) was the most frequent sign. Eleven cases underwent surgery. Five cases of choledochal cyst (m=0, f=5) were included in this study. Abdominal pain and vomiting was the most common clinical manifestation in cases with choledocal cyst. Conclusion: Jaundice, acholic stool, and dark brown urine were the most frequent clinical manifestation in cases with biliary atresia. Mean age at the time of diagnosis and operation for biliary atresia was 82.11 days (30 days- 6.5 months). Abdominal pain was the most frequent sign of cholecystitis. Early referral and more experience are needed in order to increase survival of biliary atresia cases in our hospital.